Mental and physical well-being in oncology-hematology–unit personnel. Issue 6 (2nd November 2018) - Magnavita, Nicola; Sestili, Cristina; Mannocci, Alice; Ercoli, Elisa; Boccia, Antonia; Bonaga, Gloria; Sica, Simona; Maurici, Massimo; Alvaro, Rosaria; Sili, Alessandro; Cartoni, Claudio; La Torre, Giuseppe
ABSTRACT: Health care workers (HCWs) in university hematology units (UHUs) face high job demand that can have adverse health effects. This cross-sectional study investigated the relationship between some job stressors and health-related quality of life among HCWs of 3 UHUs in Rome. Work-related stress was measured with the Demand–Control Questionnaire; health-related functioning with the mental component score (MCS) and physical component score (PCS) of the Short Form 12 Survey; positivity with the Positivity Scale. Data of 201 respondents were analyzed. Job demand was inversely associated with MCS ( p = .05) and PCS ( p = .049); job control was directly associated with PCS ( p < .001) and MCS ( p = .024). A high positivity scale score and high decision latitude score predicted high MCS and PCS. High job demand score predicted low MCS and PCS scores. Reduced job stressors and enhanced positive attitudes can improve HCWs' health-related quality of life.